2021
DOI: 10.1111/and.13978
|View full text |Cite
|
Sign up to set email alerts
|

Iprodione and chlorpyrifos induce testicular damage, oxidative stress, apoptosis and suppression of steroidogenic‐ and spermatogenic‐related genes in immature male albino rats

Abstract: The fungicide iprodione (IPR) and the insecticide chlorpyrifos (CPF) are concurrently applied for early disease control in fruits and other crops. However, there are no available data about the impacts of their co‐exposure. Additionally, IPR and CPF are known as endocrine disruptors that can cause reproductive toxicity. The outcomes of their co‐exposure on the development of male reproductive organs are still unknown. Therefore, this study aimed to assess the risk of exposure to these pesticides, particularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…CPF-treated animals exhibit an oxidant/antioxidant imbalance in testis tissues, as evidenced by elevated MDA levels and decreased GSH, SOD, and TAC. The authors of [ 50 ] reported similar results. Reactive oxygen species (ROS) adversely affect the genetic content of spermatozoa and, thus, impair sperm survival and function.…”
Section: Discussionsupporting
confidence: 56%
“…CPF-treated animals exhibit an oxidant/antioxidant imbalance in testis tissues, as evidenced by elevated MDA levels and decreased GSH, SOD, and TAC. The authors of [ 50 ] reported similar results. Reactive oxygen species (ROS) adversely affect the genetic content of spermatozoa and, thus, impair sperm survival and function.…”
Section: Discussionsupporting
confidence: 56%
“…The process of sperm production is known to be controlled by the three leading male fertility hormones: TES, FSH, and LH [75]. Our data revealed that Fe 2 O 3 -NPs exposure markedly decreased the male sexual hormones, including TES, FSH, and LH levels in the male rats.…”
Section: Discussionmentioning
confidence: 55%
“…In the studies we retrieved, chlorpyrifos was administered at only one dose level; studies that permit a dose-response analysis could not be located. Babazadeh and Najafi (2017) observed declines in semen quality in rats that received 37 mg/kg/d, Alaa-Eldin, et al (2017) and Hassan et al, (2021) saw similar effects at 6.5 mg/kg/d. The lowest reported dose for declines in semen quality was 3 mg/kg/d, given to adult rats over 20 weeks (Li et al, 2019).…”
Section: Chlorpyrifosmentioning
confidence: 90%